Linear Weingarten factorable surfaces in isotropic spaces - Aydin, Muhittin Evren; Ogrenmis, Alper Osman (Univ Babes-Bolyai, 2017)
In this paper, we deal with a certain factorable surface in the isotropic 3-space satisfying aK +bH = c, where K is the relative curvature, H the isotropic mean curvature and a, b, c is an element of R. We obtain a complete classification for such surfaces. As a further study, we prove that a certain graph surface with K = H-2 is either a non-isotropic plane or a parabolic sphere.
Keywords: Isotropic space; factorable surface; Weingarten surface; Euler inequality